Challenges of Agri-Start-ups in Post-Harvest Cold Storage Technologies - Kumar, Alok; Ganesha, T. B.; Mishra, B. P.; Venkatesan, P.; Kumar, Sanjiv; Meena, P. C.; Prakash, Satya; Gupta, B. K. (Indian Journal of Extension Education, 2021)
Agri-start-ups are developing new products through a value chain, supply chain solutions, packaging, processing systems, infrastructure, warehousing, logistics, protection of foodstuffs, communications, e-commerce, delivery and retail models. The study aims to document the challenges of Agri-startups working in post-harvest and storage parameters of fruits and vegetables. To get the insight, primary and secondary survey was carried out and data was used to provide suggestions to capture the customer and market. The data indicated that different units required different temperature range to store a different kind of commodity in their cold storage unit. 86.15 per cent of units were using the backup generators. 53.84 per cent of units were getting the commodities directly from farmers, 30.76 per cent from traders, 9.24 per cent from both and 6.15 per cent from others. 50.76 per cent of units were desired to get low electricity bill and 10.76 per cent of units were desired to come out of usage of generator whereas 32.3 per cent of units were willing to get both i.e. low electricity bill and without dependency on generator and 6.15 per cent of units were willing to reduce other costs like operation cost, maintenance cost etc. 70.76 per cent of cold storage units having a cooling tower.
Keywords: Agri-startups; Cold storage; Horticulture; Post-harvest; Technologies